How to promote grass roots medical treatment under China's graded diagnosis and treatment policy? — From the perspective of customer value theory - Tao, Wanqiong; Chen, Xiangrui; Gan, Shuyu (Frontiers in Public Health, 2022)
Objectives Based on the background of the implementation of graded diagnosis and treatment policy (GDT) in China, this paper studied the service optimization of primary medical institutions from the perspective of the primary medical treatment rate. Methods First, the difference-in-difference (DID) empirical strategy is used to analyze the impact of the implementation of the GDT on the improvement of the primary medical attendance rate, and the parallel trend test and the placebo test were used to test the robustness to illustrate the necessity of policy implementation. Second, combined with customer value theory, this paper used a logistic regression model to study the impact of customer value perception on grassroots medical care. Results The implementation of the GDT can indeed improve the rate of primary care (p = 0.028), but the impact is relatively small (0.042). From the perspective of value perception hierarchy, emotional value perception (p < 0.05) is the key factor that affects the behavior of grassroots medical treatment at this stage. Conclusion This paper fills the gaps in existing research, including empirical research on the grassroots medical treatment behavior of the masses under GDT and the impact of value perception on grassroots medical behavior. Furthermore, the recommendations are made for primary care institutions based on the results of the analysis, which promote the advancement of primary care services in China.